PERKAWINAN ANAK SEBUAH KRIMINAL ? - Abdul Basir, Muchammad; Nugraha, Alfajar (Al-Usroh : Jurnal Hukum Keluarga Islam, 2023)
The problem of child marriage does not only occur in Indonesia but in all parts of the world still have problems In child marriage, in child marriage there are often violations in the form of discrimination related to children's rights even if the violation is a crime for the parties involved because there is a criminal threat in it. Therefore, in this case, the author will analyze the extent of criminal elements that occur in child marriage by examining based on the theory of the state of law and the theory of punishment related to child marriage. This research was conducted qualitatively using a normative juridical approach. Qualitative methods are used to understand and explain social phenomena or human behaviour. The focus is on context, meaning, and interpretation of the data. This approach focuses on how principles or standards are used in positive law. Based on the results of the author's analysis several criminal elements can be criminalized related to child marriage, namely as contained in articles 287-288 of the Criminal Code with subjective and objective elements, namely the woman who is by the husband is his wife, who is not yet married and causes injuries then threatened criminally and in article 26 paragraph (1) point c of the Child Protection Law,  Parents have violated children's rights by not trying to prevent marriage at the age of children. So that everyone, including parents who intentionally or unintentionally have committed acts of discrimination against children which results in children experiencing both material and moral losses so that their social functions or neglect of children that cause children to experience pain or suffering, both physical, mental and social, are threatened with crime which in this case can be associated as forced marriage by examining that a child cannot provide Informed consent so that the possibility of marriage being coerced in the form of persuasion from someone, both parents, family, and other people is a form of discrimination.